Criticism of “fascist nostalgia” in the political thought of the New Right - Sondel-Cedarmas, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The article analyses the way in which the Italian New Right perceived fascist traditions as cultivated by the Italian Social Movement Movimento Sociale Italiano. The New Right that was shaped in the period of student protests and marches in the 1960s and 1970s among the youth environment of the MSI strived for the ideological renewal of this party, in particular seeking to discard the so-called “Fascist Nostalgia” that had been dooming it to political exclusion. The party principally rejected Julius Evola’s integral traditionalism, which had been a point of reference for neo-fascist circles, and castigated the absence of contemporary cultural and ideological patterns of the Italian far right. Under the infl uence of the French idea of “Nouvelle Droit”, the Italian New Right was meant to be a metapolitical programme that assumed expanding of the traditional electorate with a simultaneous and direct impact on the civil society through taking up contemporary social and cultural topics, as well as fi ghting traditional dichotomy of the right and the left.
Keywords: nowe prawo; faszystowska nostalgia; włoski ruch społeczny